2021
DOI: 10.1186/s12576-021-00793-2
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CASC7 inhibits the proliferation and migration of papillary thyroid cancer cells by inhibiting miR-34a-5p

Abstract: Long noncoding RNAs (lncRNAs) play an essential role in the progression of papillary thyroid cancer (PTC). However, the expression and function of lncRNA cancer susceptibility candidate 7 (CASC7) in PTC remain unknown. The purpose of this study was to investigate the role and molecular mechanism of CASC7 in regulating PTC cell behavior. The expression of CASC7, miR-34a-5p, and tumor protein P73 (TP73) was determined by qRT-PCR and western blot. Cell proliferation was examined by MTT assay. Cell apoptosis was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Prior research demonstrated that lncRNAs might operate as a miRNA sponge, modulating the miRNA expression and competing for miRNA (22). By targeting miR-34a-5p, CASC7 restricts the proliferation and migration of papillary thyroid cancer cells (23), and by downregulating miR-10a, CASC7 may upregulate phosphatase and tensin homolog to restrict neuroblastoma cell growth (24). CASC7 prevents colon cancer cell growth and migration via restricting miRNA-21 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research demonstrated that lncRNAs might operate as a miRNA sponge, modulating the miRNA expression and competing for miRNA (22). By targeting miR-34a-5p, CASC7 restricts the proliferation and migration of papillary thyroid cancer cells (23), and by downregulating miR-10a, CASC7 may upregulate phosphatase and tensin homolog to restrict neuroblastoma cell growth (24). CASC7 prevents colon cancer cell growth and migration via restricting miRNA-21 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have revealed the role of CASC7 in other cancers and pathologies. It was reported that CASC7 retarded the progression of multiple cancers, such as papillary thyroid carcinoma, neuroblastoma, glioma and non-small-cell lung cancer [ 9 , 10 , 26 , 27 ]. All these researches uniformly pointed out that lncRNA CASC7 is a cancer suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many lncRNAs, lncRNA CASC7 (cancer susceptibility candidate 7) is an RNA gene and is affiliated with the lncRNA class [ 8 ]. It has been previously reported that lncRNA CASC7 functions as a tumor suppressor in both non-small-cell lung cancer and thyroid cancer [ 9 , 10 ]. Besides, lncRNA CASC7 is associated with several pathologies, such as heart failure and severe asthma [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… Diagnosis 4 cell lines China 2019 Lu [ 119 ] miR-34a-5p TP73 CASC7 suppressed the PTC cell proliferation and migration by miR-34a-5p sponging and TP73 up regulation. Diagnosis 30 patients 2 cell lines China 2021 Sun [ 120 ] miR-214 PSMD10 MiR-214 suppressed PTC cell migration and EMT via PSMD10 targeting. Diagnosis and prognosis 30 patients 2 cell lines China 2018 Liu [ 121 ] miR-4319 SMURF1 MiR-4319 repressed the TC cell migration and EMT through SMURF1 targeting.…”
Section: Introductionmentioning
confidence: 99%
“…TP73 belongs to the p53 protein family that is involved in cell cycle and apoptosis regulation. CASC7 suppressed the PTC cell proliferation and migration by miR-34a-5p sponging and TP73 up regulation [ 120 ].…”
Section: Introductionmentioning
confidence: 99%